Inovasi Sistem Robotika Pada Perpustakaan - Irzaldi Adi Darmanto (Journal of Electrical Engineering and Computer (JEECOM), 2020)
The challenge of libraries in the current millennium is how the library can make it easier for visitors to find books in a short time. At this time the development of new technology is needed, especially in the 21st century all work will be replaced with a robot. this robot technology that began today was developed by several parties for the advancement of human civilization. In this journal, we will discuss how robot technology works in the scope of the library and how robots can work as instructed. The results showed, there are several world libraries that have used robotic technology that makes it easy for library visitors to find, retrieve and return books on the library shelves.